2020
DOI: 10.1177/0300060520925996
|View full text |Cite
|
Sign up to set email alerts
|

The anti-alcohol dependency drug disulfiram inhibits the viability and progression of gastric cancer cells by regulating the Wnt and NF-κB pathways

Abstract: Objective Disulfiram is commonly used for alcohol abuse; however, recent studies have revealed its potential as an anti-cancer treatment. This study investigated the effects of disulfiram on gastric cancer and its underlying mechanisms of action. Methods The gastric cancer cell lines MKN-45 and SGC-7901 were used for all experiments. Cell proliferation was investigated using cell counting kit-8, cell migration and invasion were examined using Transwell assays, the proliferation and metastasis related proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 24 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…DSF/Cu complex has been reported to suppress the growth and metastasis of non-small-cell lung cancer (NSCLC), hepatocellular carcinoma, and oral squamous cell carcinoma (6,19,20). Zhang et al found that disulfiram repressed the viability and progression of gastric cancer cells, and inhibited the expression of Wnt/b-catenin by ELISA (21). Therefore, we aimed at exploring the anti-cancer activity of DSF/ Cu complex using MKN-45 and BGC-823 GC cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DSF/Cu complex has been reported to suppress the growth and metastasis of non-small-cell lung cancer (NSCLC), hepatocellular carcinoma, and oral squamous cell carcinoma (6,19,20). Zhang et al found that disulfiram repressed the viability and progression of gastric cancer cells, and inhibited the expression of Wnt/b-catenin by ELISA (21). Therefore, we aimed at exploring the anti-cancer activity of DSF/ Cu complex using MKN-45 and BGC-823 GC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al. found that disulfiram repressed the viability and progression of gastric cancer cells, and inhibited the expression of Wnt/β-catenin by ELISA ( 21 ). Therefore, we aimed at exploring the anti-cancer activity of DSF/Cu complex using MKN-45 and BGC-823 GC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Despite showing promising results in experimental models, bortezomib has not been used for therapy of human GC. Interestingly, disulfiram, a well-known drug for treatment of chronic alcoholism, can inhibit the 26S proteasome and NF-κB activity and demonstrate anti-tumor activities [ 163 ].…”
Section: Therapeutic Targeting Of Nf-κb In Gastric Cancermentioning
confidence: 99%
“…In 2017, Karamanakos’ groups treated a GBM patient with DSF in combination with the standard of care and improved progression-free and overall survival [ 28 ]. Although DSF has been suggested as an anti-tumor agent [ 40 , 41 , 42 ], and a phase II clinical trial indicated that DSF is safe and is well-tolerated, combining TMZ and DSF did not significantly improve the prognosis of recurrent GBM patients [ 43 ]. In addition, various studies have indicated that DSF may be a good sensitizer for radio- and chemotherapy [ 44 ].…”
Section: Discussionmentioning
confidence: 99%